PENGARUH HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN DI ANDINI KONVEKSI - Audina, Viola; Suarman, Suarman; RM Riadi, RM Riadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to determine the effect, price, and promotion of purchasing decisions at Andini Convection. The number of samples used in this study were 72 consumers who had made purchases more than three times. The type of data used in this study is primary data in the form of prices, promotions and purchasing decisions. Data collection method using a questionnaire. The analysis technique used in this study is multiple linear regression analysis. The results showed that there was a significant effect between price and promotion on purchasing decisions at Andini Convection Key Words: Price, Promotion, and Purchase Decision